The Role of Witnesses in Prosecuting Cases of Fatal Assault: Legal and Sociological Perspectives - Reni Berlian Silalahi; Ira Yenita Malau; Rani Sabeta Nainggolan; Mhd Ilham Hidayat Rastami; Parlaungan Gabriel Siahaan; Dewi Pika Lumban Batu (JURNAL HUKUM SEHASEN, 2023)
The act of physical assault is one of the persistent phenomena that is difficult to eradicate in society. Various acts of violence, such as physical abuse and battery, often result in injuries to the victim's body or body parts, and sometimes even lead to lifelong physical disabilities or, in severe cases, death. In criminal cases, witnesses hold a crucial position in determining prosecution, as they are considered lawful instruments. This study examines the role of witnesses in the prosecution of cases of fatal assault. The research method employed in this study is normative legal research, also known as doctrinal legal research or library-based legal research. This type of research is conducted by examining secondary data, including primary legal materials, secondary legal materials, and tertiary legal materials. Based on the research findings, it can be concluded that witnesses play a significant and pivotal role in uncovering the truth and facilitating prosecution. From both legal and sociological perspectives, the role of witnesses includes providing evidence, giving testimony, and supporting the public prosecutor. As such, it can be concluded that witnesses have an important role in prosecution, as stipulated in Article 184 paragraph (1) of the Criminal Code.